Dilemmas of outsourcing end-activities in the public sector, based on constitutional principles (Revista Direito em Debate, 2023)
The qualitative theoretical and jurisprudential research undertaken has as scope concepts and definitions about outsourcing, to evaluate its applicability in the national Public Administration, with special reference to cogent constitutional principles. The object of the analysis is the existing dichotomy between “middle activities” and “end activities” in the view of the Brazilian Higher Courts. It is believed, by hypothesis, that outsourcing in public services has limits, on the type of activity to be developed, whether medium or final. The theoretical analysis is concerned with the results of the jurisprudential trend, in the last decade, to answer the central question, about the constitutionality (or not) of outsourcing end-activities in the public sector, concluding that such practice is unconstitutional, if unrestricted.